Association between contraceptive implant knowledge and intent with implant uptake among postpartum Malawian women: a prospective cohort study. Issue 1 (December 2016) - Tang, Jennifer; Kopp, Dawn; Stuart, Gretchen; O'Shea, Michele; Stanley, Christopher; Hosseinipour, Mina; Miller, William; Mwale, Mwawi; Kaliti, Stephen; Bonongwe, Phylos; Rosenberg, Nora
Abstract Background Long-acting reversible contraception (LARC) can assist women with birth spacing and reduce unintended pregnancies. Sub-Saharan Africa has low uptake of the two available methods of LARC, the subdermal implant and intrauterine contraception (IUC). Our primary objectives were to: 1) calculate the incidence of LARC use among postpartum Malawian women, and 2) assess if LARC knowledge and intent to use LARC were associated with LARC uptake. Methods This study was a prospective cohort study of 634 postpartum women who were recruited from the postpartum ward of Bwaila Hospital in Lilongwe, Malawi. Study participants completed a baseline survey in the postpartum ward. Follow-up telephone surveys about contraceptive use were conducted at 3, 6, and 12 months postpartum. Cox proportional hazards regression analysis was performed to evaluate if implant knowledge and intent to use implant were associated with implant uptake. Results One hundred thirty-seven implant and 10 IUC placements were reported over 12 months of follow-up; given the low rate of IUC uptake, further analysis was only done for implant uptake. The incidence rate for implant uptake was 35.6 per 100 person-years (95 % CI 30.0, 42.2). Correct implant knowledge (adjusted HR = 1.69; 95 % CI 1.06, 2.68) and intent to use implant (adjusted HR 1.95; 95 % CI 1.28, 2.98) were both associated with implant uptake. Conclusions More women reported implant use than IUC use in our study. Correct implant knowledge and intent to use implant were both associated with implant uptake, with a stronger association for intent. Interventions to increase LARC uptake should focus on improving LARC knowledge and removing barriers to LARC. Trial registration Clinical Trial Registration #:NCT01893021